1987
DOI: 10.1126/science.238.4824.205
|View full text |Cite
|
Sign up to set email alerts
|

An Amylose Antiparallel Double Helix at Atomic Resolution

Abstract: In the crystal structure of the polyiodide complex (p-nitrophenyl-alpha-maltohexaose(2)) . Ba(I(3))(2) . 22H(2)O, the maltohexaose units form an antiparallel, left-handed double helix with O-2 ... O-3 and O-6 ... O-6 hydrogen bonding and a central cavity that encloses two triiodide units. This structure contrasts with the parallel, left-handed double helix with no central cavity proposed for the A-and B-starch helix and the left-handed single helix in V-amylose and may be relevant for the stabilization of glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 27 publications
4
50
0
3
Order By: Relevance
“…The coordination of the water molecules to CA26 follows patterns that have been observed previously (9,10,12,18). The most prominent motifs are five-membered rings formed by water molecules coordinated in bidentate mode to O(2) and O(3) and͞or to O(5) and O(6) belonging to the same glucose.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…The coordination of the water molecules to CA26 follows patterns that have been observed previously (9,10,12,18). The most prominent motifs are five-membered rings formed by water molecules coordinated in bidentate mode to O(2) and O(3) and͞or to O(5) and O(6) belonging to the same glucose.…”
Section: Resultssupporting
confidence: 66%
“…Since crystallization of amylose fragments with defined chain lengths has remained elusive, structural information relies on x-ray fiber diffraction, electron diffraction on tiny single crystals, and solid-state 13 C cross-polarization͞magic angle spinning (CP͞MAS) NMR spectroscopy combined with computer-aided modeling (3)(4)(5)(6)(7)(8). The only available single crystal x-ray study of an amylose-type oligosaccharide in the complex (p-nitrophenyl ␣-maltohexaoside) 2 ⅐Ba(I 3 ) 2 ⅐27H 2 O features an antiparallel left-handed double helix (9,10) that has no resemblance to A-, B-, or V-amylose.…”
mentioning
confidence: 99%
“…In addition, all glucoses assume a favorable 4 C 1 chair conformation, except for those that bind in subsite Ϫ1 (7). However, the internal hydrogen bond network between the glucose OH-2 and OH-3 groups, which is observed in both free cyclodextrins (24,31) and free starch (32), is broken between subsites Ϫ1/ϩ1 and ϩ1/ϩ2 (see Table III and Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…9 shows that either conformation in linear amylose could potentially allow cyclization to form cycloamylose in either configuration. The Monte Carlo simulation suggested that the antiparallel double helix structure is the most likely conformation of amylose in solution (21), and crystallographic analysis has shown that linear amylose with a DP of 6 adopts a left-handed antiparallel double helix conformation (22,23). It can be seen how such a conformation would readily allow cyclization by D-enzyme since donor and acceptor sites of amylose are juxtaposed (Fig.…”
Section: Figmentioning
confidence: 99%